How Does PM2.5 Impact the Urban Vertical Temperature Structure? A Case Study in Nanjing - Hao Wu; Yang Cao; Tijian Wang; Jiawei You; Tingting Yang; Yawei Qu; Shuqi Yan; Huadong Yang; Xiyu Mu; Libo Gao; Congwu Huang (Aerosol and Air Quality Research)
Abstract PM2.5 impacts the atmospheric temperature structure through scattering or absorbing solar radiation, whose concentration and composition can affect the impact. This study calculated the effect of PM2.5 on the temperature structures in the urban centre and the suburbs of Nanjing, as well as their differences. The results show that the optical parameters, atmospheric heating rate, radiative forcing, and temperature are all impacted by the concentration and composition of PM2.5. The uneven distribution of PM2.5 influences the differences in those factors between the urban centre and suburbs. In spring, summer, autumn, and winter, surface temperatures in the urban centre were approximately 283 K, 285 K, 305 K, and 277 K, while those in the suburbs were approximately 282 K, 283 K, 304 K, and 274 K. The urban heat island intensity has been reduced by 0.1–0.4 K due to the presence of PM2.5 in Nanjing. Due to the black carbon component’s warming effect on the top of the boundary layer, the impact of PM2.5 on the urban heat island intensity profile drops quickly at the 0.75–1.25 km. PM2.5 may mask the “warm city” problem and have a more complex impact on the urban climate.